Processes that shape the earth - Thompson, David M. 1977- (Physics in action (New York, N.Y.), 2007)
On Earth, nothing is still. Mountains rise and fall. Tides ebb and flow. Even the continents themselves are on the move. Beneath the surface, a nuclear engine powers earthquakes, volcanic eruptions, and the shifting of continents. Above ground, the sun causes the wind to howl, rain to pour, rivers to churn, and oceans to swell with waves. Processes That Shape the Earth surveys these forces and the ways they sculpt the planet. The modern theory of plate tectonics is introduced, along with other pertinent topics in physical geology. Several chapters add relevant historical context, presenting re.